Electrocardiographic Comparison Between Artificial Cardiac Stimulation of Apex, Septum and Right Ventricular Outflow Tract - Coello, Roberto Carlos Alvarez; Piedra, Diego Patricio Serrano (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Background: Ventricular pacing is detrimental to cardiac function, with more deleterious effects when it is apical, widening the QRS complex, so the best cardiac pacing site is still being sought. Objective: To compare, by electrocardiographic measurements, the duration of QRS complexes at different cardiac stimulation sites, from the medical records of patients with pacemakers, who attended the external cardiac stimulation consultation at Monte Sinai Hospital in Cuenca-Ecuador. Methods: A total of 323 patients were retrospectively analyzed from January 2011 to November 2018, classifying them by electrocardiographic morphology as apical, low septal, middle septal and right ventricular outflow tract (RVOT) stimulation. The duration of stimulated QRS complexes was quantified using digital software that allows such measurement and stores all records. Subsequently, the comparison of the means of the different stimulation sites was performed using ANOVA. Results: The average age was 73.6 years; 56.03% corresponded to males; 49.84% had apical stimulation, 21.67% middle septal, 15.78% RVOT, 12.69% low septal. At the end of the QRS complex measurements, an average on apex of 179.94 ms, on low septum of 172.56 ms, an average on middle septum of 153.89 ms and on RVOT 171.66 ms were obtained. When comparing these values with the average ANOVA, the duration of the QRS stimulated in the middle septum was shorter than the other sites, being statistically significant (p < 0.001). Conclusion: Cardiac pacing in the middle septum is a viable alternative, which results in shorter QRS complex duration, therefore, better synchronization of myocardial contraction, also avoiding the deleterious effects of apical stimulation.